2019
DOI: 10.1177/2309499019866965
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of mortality of patients with fragility hip fractures at 1 year after discharge: A multicenter, retrospective study in the northern Kyushu district of Japan

Abstract: Creative Commons Non Commercial CC BY-NC: This article is distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 License (http://www.creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access pages (https://us.sagepub.com/en-us/nam/open-access-at-sage). AbstractPurpose: Fragility hip fractures (FHFs) are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…These factors would have precluded adequate medical visits after treatment for FHF, resulting in an extremely low osteoporosis medication rate. Moreover, in our previous study, patients with low independence at discharge from the hospital after FHF treatment had a significantly lower survival rate after 1 year of fracture [16]. Therefore, after FHF treatment, active rehabilitation and improvement of the general conditions should be considered to increase the level of patient independence as much as possible.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These factors would have precluded adequate medical visits after treatment for FHF, resulting in an extremely low osteoporosis medication rate. Moreover, in our previous study, patients with low independence at discharge from the hospital after FHF treatment had a significantly lower survival rate after 1 year of fracture [16]. Therefore, after FHF treatment, active rehabilitation and improvement of the general conditions should be considered to increase the level of patient independence as much as possible.…”
Section: Discussionmentioning
confidence: 92%
“…The exclusion criteria included high-energy trauma and pathological fractures. As described in our previous study [1,16], to construct the FHF registry, the clinical data of eligible patients were submitted by each participating hospital to the data centre at the Kyushu University Hospital via the Clinical Research Internet Network (CRIN-Q) developed by the Kyushu University Hospital. Our 17 affiliated hospitals are all general hospitals with multiple departments and acute care that mainly provide surgical treatment for FHF.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study aiming to identify predictors of 1-year mortality in FHF patients showed that previous vertebral fracture and Barthel Index (BI) < 30 were found to increase risk of death for male patients. 7 Meanwhile, BMI < 18.5 kg/m 2 , Total Charlson Comorbidity Index (TCCI) of 5, smoking history, length of stay (LOS) < 14 days, and BI < 30 were the risk factors for female patients. 7 Fracture Liaison Service (FLS) is a coordinated multidisciplinary program, targeting the facilities available under the healthcare system, to prevent secondary fracture.…”
mentioning
confidence: 99%
“…7 Meanwhile, BMI < 18.5 kg/m 2 , Total Charlson Comorbidity Index (TCCI) of 5, smoking history, length of stay (LOS) < 14 days, and BI < 30 were the risk factors for female patients. 7 Fracture Liaison Service (FLS) is a coordinated multidisciplinary program, targeting the facilities available under the healthcare system, to prevent secondary fracture. To date, there are one hundred and thirty-five FLS from thirteen countries/regions in Asia Pacific mapped on the "Capture the Fracture CtF" Map of Best Practice.…”
mentioning
confidence: 99%